A computational fluid dynamics of blood flow in cerebral saccular aneurysm / Azali Daud - Daud, Azali (2010)
The significance of this project is to expose me into CATIA V5R17 software and CFD software (Cd Adapco) environment. Therefore the combination of these two computational engineering tools will help to develop skills of designing the products from sketch to finishing. On the other hand, computational fluid dynamics will contribute the experience in numerical solutions involving analyzing problems of fluid flow and heat transfer through computational simulations By Using CFD analysis hopefully it can provide the guidance for surgical intervention decision making in some of the more questionable cases in cerebral aneurysm, the aneurysm characteristics can be analyzed and allow medical professionals to determine if an aneurysm is at risk of rupture. The simulated images will show the contours of pressure and wall shear stress on the aneurysms walls. The medical professional also can know whether surgery is wanted or not to reduce the risk of cerebral aneurysm amongst specific patients.